At Home in the World : California Women and the Postwar Environmental Movement - Cairns, Kathleen A., 1946- (Book collections on Project MUSE., 2021)
"At Home in the World examines the extraordinary significant--and largely unheralded--role women played in forging the modern environmental movement, specifically in California"--